Implementasi Pelaksanaan Perlindungan Varietas Tanaman di Australia - Putra Rezki Dewanto (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to determine the implementation of plant variety protection in Australia. This article will discuss how Australia implements the TRIPs Agreement to provide protection for all technologies, products, pharmaceuticals, plants, and microorganisms that can be patented through Plant Breeder's Rights (PBR). There are three types of intellectual property obtained in the context of plant varieties, namely patent rights, trademark rights, and plant breeding rights. The purpose of protection through PBR is to encourage innovation in plant breeding by granting limited exclusive rights to control its exploitation and prevent unauthorized parties from illegally exploiting the rights of breeders. The research method used in this study is normative law research, employing a statutory approach and an analytical approach.